The school knowledge about health in physical education: A review - Oliveira, João Paulo (2017)
Health has always marked the History of Physical Education, directing its speech at school. Currently, this discussion has recovered the relevance of health approach at school, trying to rethink its inclusion as a subject to be addressed within Physical Education. In this context, it was our goal to analyse the academic literature about the school health knowledge within physical education. For this we conducted a systematic review study with a statistical survey and qualitative nature of analysis. We define the period of 2008-2014 to collect data, using as database for Periodicals of Physical Education WebQualis system of CAPES, which were treated by categorical analysis technique and by themes. We found that the studies relating School Physical Education and Health identify points about the constitution (selection, organization and systematization) of school knowledge, although the focus of their research were not these. We recognize that the issue of school curriculum in Physical Education, especially around the school knowledge of health has been marked as a potentially important research field to be explored by researchers.